Perancangan Interior Instalasi Gawat Darurat untuk Anak – anak di Surabaya - Vonny Popo Sudibyo; Sherly de Yong; Purnama Esa Dora Tedjokoesomo (Intra, 2018)
Health services in Indonesia are provided through public hospitals and specialist hospital to optimize the health service for society. However, the health services for children in Indonesia is poorly maintained, whilst the emergency room design in the hospital could affect the patient’s psychology and well-being. Besides the facilities, another aspect in an emergency room that could accelerate the patient’s healing progress are colors, interior materials, textured, lighting, indoor air condition, and scenery. The design method consists of some steps such as inquiry, empathize, define, brainstorm, prototype, test, apply, and reflect. The emergency room is designed for infants and children (0-14 years old) with an attractive design which suitable for children. The design concept is Enjoyable Active, which could create a playful, energetic, cheerful, and warm emergency room atmosphere. The main colors of this design are: green, to lower the stress; beige, to give a cheerful atmosphere and neutralize nervous feeling in patients; and blue which provide a calming nuance. Other facilities in the design are information area, registration area, playground, register area, pharmacy, and radiology area which are reachable in the emergency room.